Expected years of life lost through road traffic injuries in Mexico - Efrén Murillo-Zamora; Oliver Mendoza-Cano; Benjamín Trujillo-Hernández; José Guzmán-Esquivel; Alfredo Medina-González; Miguel Huerta; Ramón Alberto Sánchez-Piña; Agustin Lugo-Radillo (Taylor & Francis Group, 2017)
Background: Road traffic injuries (RTIs) are a leading cause of premature mortality, mainly in low- and middle-income countries Objective: To estimate the 2014 burden of RTIs in Mexico calculating years of life lost (YLL) and age-standardized YLL rates (ASYLL), and to evaluate sex, age, and region-related differences in premature mortality. Methods: Mortality data were obtained from the National Institute of Statistics and Geography and 14,637 deaths of individuals 15 years of age and older were analyzed. The YLL and ASYLL were computed. Results: The overall burden of RTIs was 332,922 YLL and 82.4% of the deaths occurred in males. Males from 25 to 34 years of age and females from 15 to 24 years of age showed the highest age-adjusted YLL rates (933 and 158 YLL per 100,000 inhabitants, respectively). The national ASYLL rate was 416 per 100,000 inhabitants and the highest state-stratified mortality rates were observed in Tabasco (851), Sinaloa (709), Durango (656), Zacatecas (642), and Baja California Sur (570). Conclusions: RTIs contributed to the premature mortality rate in the study population. Our findings may be useful from a health policy perspective for designing and prioritizing interventions focused on the prevention of premature loss of life.